2011
DOI: 10.1029/2011jd015803
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a 4 year radiosonde data set at Dome C for characterizing temperature and moisture conditions of the Antarctic atmosphere

Abstract: [1] A 4 year set of vertical profiles of pressure, temperature and relative humidity derived from 1113 radiosounding measurements performed at Dome C (Antarctica) at 12:00 UTC of each day, from late March 2005 to March 2009, were analyzed using an updated procedure for removing the most important temperature and humidity errors and dry biases. The monthly mean vertical profiles of pressure, temperature, and moisture parameters were determined, providing evidence of the strong seasonal variations in temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
65
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(74 citation statements)
references
References 70 publications
(158 reference statements)
8
65
0
1
Order By: Relevance
“…It is important to note that the 630-470 hPa layer is located between the ground and an altitude of ∟ 2 km which maximizes the calculation of IWV. A 1.2 K cold bias is also observed in the RS92 from the surface up to an altitude of ∟ 4 km (Tomasi et al, 2011(Tomasi et al, , 2012.…”
Section: Radiosondesmentioning
confidence: 82%
See 1 more Smart Citation
“…It is important to note that the 630-470 hPa layer is located between the ground and an altitude of ∟ 2 km which maximizes the calculation of IWV. A 1.2 K cold bias is also observed in the RS92 from the surface up to an altitude of ∟ 4 km (Tomasi et al, 2011(Tomasi et al, , 2012.…”
Section: Radiosondesmentioning
confidence: 82%
“…We recall that the corrections performed on the radiosonde data measured in 2009 according to Miloshevish et al (2006) shown a weak impact (with a maximum of +4 % on IWV) on the vertical profiles (Ricaud et al, 2013). Furthermore, considering the updated tools developed in Miloshevich et al (2009) and Tomasi et al (2011Tomasi et al ( , 2012 found that, between 630 and 470 hPa, the correction factor for humidity estimated by the radiosonde varied within 1.10-1.15 for daytime and within 0.98-1.00 for night-time. It is important to note that the 630-470 hPa layer is located between the ground and an altitude of ∟ 2 km which maximizes the calculation of IWV.…”
Section: Radiosondesmentioning
confidence: 99%
“…The radiosounding datasets were based on measurements made at Ny-Ålesund (~79°N) during June-July of 2000-2003 [24], and at Mario Zucchelli (~75°S) during the austral summer season from 1987 to 1998 [25]. Above 30 km altitude, the profiles were completed with (i) monthly mean vertical profiles of the three thermodynamic parameters obtained by Tomasi et al [31] from multi-year Michaelson Interferometer for Passive Atmospheric Sounding (MIPAS)-Environmental Satellite (ENVISAT) limb-scanning measurements over the 33-60 km altitude range at 80°N in July and at 75°S in January, and (ii) the vertical profiles p(z) and T(z) defined in the AFGL Subarctic Summer model over the 70-120 km altitude range [27]. The combined average vertical profiles of p(z), T(z) and e(z) were used in the Tomasi et al [23] algorithm to calculate the vertical profiles of n(z) in the Arctic and Antarctic atmospheres.…”
Section: The Atmospheric Model Used To Calculate the Relative Opticalmentioning
confidence: 99%
“…In the present study, ma(θ) was calculated using Equation (3) with the values of n(z) and no derived from the following radiosounding datasets and meteorological data recorded at the following sites: [31].…”
Section: The Atmospheric Model Used To Calculate the Relative Opticalmentioning
confidence: 99%
“…Miloshevich et al (2009) provides a comprehensive correction algorithm for the RS92 humidity profiles, taking into account the effects of calibration errors, time lag (slow sensor response at low temperatures), and solar radiation errors. Tomasi et al (2011) analyzed 4-yr worth of radiosonde data from Dome C on the East Antarctic plateau, and applied the RS80 (Miloshevich et al 2004) and RS92 (Miloshevich et al 2009) corrections prior to characterizing the temperature and moisture fields. RS80 corrections in the lower atmosphere were appreciable (around 16% of the measured RH); however, the corrections to the RS92 profiles were less significant.…”
Section: Datasets and Study Periodmentioning
confidence: 99%